Analysis of carcass weight and proximate composition as guinea pig [Cavia porcellus (Linnaeus, 1758)] meat quality indicator - Aphrodita Adiva; Nurmalia Sentono Diva; Fitria Laksmindra (BIO Web of Conferences, 2024)
Guinea pig (GP) meat [Cavia porcellus (Linnaeus, 1758)] can serve as an alternative food due to its high protein content. GP is the staple food in Peru, thus tropical regions (Indonesia) can cultivate it. GP can be purchased at animal markets for an acceptable cost. Carcass weight and proximate analysis are required to evaluate GP meat characteristics. To examine the impact of frozen storage on meat quality, this study aimed to compare GP meat quality with chicken and catfish. The frozen meat was from commercial markets. The methodology comprised meat selection, carcass weight, proximate evaluation, and data analysis. The hind leg, thigh, and tail sections of GP, chicken, and catfish, respectively, were used for proximate evaluation and evaluated using the Titrimetric method, the Weibull method, the Oven Drying method, ash calculation, the By Difference method, and meat tenderness test. Regarding carcass weight, GP has the lowest weight. However, it has the finest proximate analysis results, compared to catfish and chicken, with a protein value of 17.42%. GP meat has potential to be gained as a high-protein food source at a reasonable cost. As opposed to chicken and catfish, more portions of GP can be consumed as meat.